Analysis of Influences on Repurchase Intentions of Pharmacy Consumers in Jakarta - Senta, Muhamad Tri Arie; Indrajaya, Sonny (Dinasti Publisher, 2024)
The aim to be achieved in this research is to determine the factors that influence the repurchase intention of pharmacy consumers in Jakarta. This research is quantitative research. The population of drug buyers at pharmacies in Jakarta is uncertain. This research used a sample of 215 pharmacy drug buyers in Jakarta for analysis. The questionnaire presents statements that respondents must choose from strongly agree to strongly disagree on a scale of 1-5 points. Hypothesis testing uses Structural Equation Model with Warp PLS. The results of several test parameters show that the sample is reliable and valid and meets the requirements. This research concludes that consumer experience has a significant and influential effect on trust. Consumer experience has a significant and influential effect on satisfaction. Consumer experience has a significant influence on repurchase intentions. Trust has a significant and influential effect on satisfaction. Trust has a significant influence on repurchase intentions. Product quality has a significant influence on trust. Product quality has a significant influence on satisfaction. Consumer experience has a significant influence on repurchase intentions through satisfaction. Satisfaction has a significant influence on repurchase intentions.